The Effect of Perceived Ease and Benefits on Intention and Behavior to use E-Learning Islamic Higher Education - Bakhri, Syaiful; Dewi Rahayu Ningsih; Imelia Sahda Salsabilla (Universitas Pendidikan Ganesha, 2025)
Although e-learning has been widely implemented in higher education institutions, the level of acceptance and actual usage among students still varies considerably. This study aims to examine the influence of perceived usefulness and perceived ease of use on students' intention to use and actual usage behavior of e-learning in Islamic public universities. A quantitative research approach was employed. The population consisted of 240 students majoring in Islamic Education Management, with 150 participants selected through stratified random sampling. Data were analyzed using outer model, inner model, and model fit tests with the assistance of PLS-SEM version 3. The findings indicate that perceived usefulness significantly influences the intention to use, perceived ease of use significantly affects the intention to use, and intention to use significantly influences actual usage behavior. Among all the tested hypotheses, intention to use had the strongest influence on usage behavior, while perceived usefulness had the weakest influence on intention to use. This study differs from previous research in its focus and the model applied to assess information system implementation. Furthermore, the types of information systems analyzed—ranging from e-learning to software or digital payment systems—also vary across studies. This research investigates the acceptance of e-learning based on four main variables: perceived usefulness, perceived ease of use, intention to use, and usage behavior, modified from the Technology Acceptance Model (TAM). The study reveals how users' perceptions affect the adoption of e-learning, providing insights for the development of more effective and user-friendly systems.